Cross-sectional study of aggression against Spanish nursing personnel and effects on somatisation of physical symptoms - María del Carmen Pérez-Fuentes; María del Mar Molero Jurado; África Martos Martínez; María del Mar Simón Márquez; Nieves Fátima Oropesa Ruiz; José Jesús Gázquez Linares (BMJ Open)
Introduction Violence against nursing personnel in their place of work is a severe problem generating important consequences for these workers. Even though there is a large body of research on the subject, the emotional impact of aggression against healthcare workers continues to be debated.Objectives The objective of this quantitative, observational cross-sectional study was to analyse the effects of aggression against nursing personnel and the mediating role of anxiety in somaticising physical symptoms.Method The sample was made up of 1357 nursing professionals who answered questionnaires evaluating their sensitivity to anxiety and the presence of somatic symptoms.Results Of the professionals who indicated that they had been the victims of aggression by family members or patients in the previous year, 52.8% said it had happened to them on one occasion, 25.2% had experienced two episodes, while 6.9% and 15.1% said they had undergone three or more aggressions, respectively. Although 89.3% of the professionals affected by acts of indicated that they had not undergone physical or psychological consequences, there was a higher prevalence of somatic alteration among workers who had been victims of violence in the workplace. Furthermore, aggression at work had a direct effect on physical somatisation, which in turn acted as a mediator in the level of anxiety of nursing professionals. Thus, aggression increased the level of anxiety of nurses through the appearance of somatic symptoms.Conclusions The results are discussed based on some of the consequences that appeared after episodes of aggression in the healthcare sector and their relationship.